Study on the prevalence of gestational diabetes mellitus at a tertiary care hospital (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2021)
The prevalence of diabetes is increasing globally. Women with Gestational Diabetes Mellitus are an ideal group for the primary prevention of diabetes as they are at increased risk of future diabetes, predominantly type 2 diabetes, as are their children. A prospective observational study was carried out in gynaecology department over a period of 6 months enrolling 150 patients. The study was carried out to identify the prevalence of GDM, to assess the prescribing pattern of anti-diabetic drugs in GDM, to identify the risk factors involved, to assess the patient’s level of knowledge about diabetes and to provide patient counselling. 106 patients were diagnosed with GDM. Most commonly prescribed anti-diabetic drugs were metformin followed by insulin. The risk factors identified were age above 30 years, obesity, family history and prediabetes. The occurrence of maternal and neonatal complications in the GDM patients were observed and most frequent complication found was caesarean in 49 cases.  The assessment of distribution of patients based on gestation period revealed that patients at gestational age of 24-26 weeks of pregnancy were more frequently diagnosed with GDM. A standard questionnaire was used to assess the level of knowledge about diabetes in GDM patients. Based on the level of knowledge, the patients were educated regarding the disease and lifestyle modification with the help of patient information leaflet. . The severity of drug interactions were evaluated and found that 13 prescriptions had major interactions, followed by 36 moderate interactions and 12 minor interactions. The present study points out the role of a clinical pharmacist in improving the patient care and overall quality of life in GDM patients.